노인의 심리·정서관련 변인과 삶의 질에 대한 메타분석 - 이명희(Myung-Hee Lee) (한국콘텐츠학회 논문지, 19(9), 2019)
The purpose of this study is to provide policy and adaptive interventions for quality of life of the elderly and evidence-based data. For this, meta-analysis was performed using CMA program, and the final 65 researches were used for analysis. The results, (1)The risk factors(depression, solitude, anxiety, suicidal Ideation, stress) showed the effect size which is suitable for quality of life. The effect size of depression was the highest. (2)The protective factors(self-esteem, self-efficacy) showed medium effect size and large effect size. Among them, self-esteem showed the greatest effect size of quality of life. However, self - control appeared to have a low effect size. 본 연구에서는 노인의 삶의 질 향상을 위한 정책과 실천적 제언을 제공하려는 목적으로 노인의 심리 정서적 변인과 노인의 삶의 질에 대한 메타분석을 실시하였다. 총 65편의 학술지 논문을 선정해 위험요인과 보호요인으로 구분하여 메타분석을 진행한 결과, 심리 정서적 변인의 위험요인은 우울, 고독, 외로움, 불안, 스트레스 순으로 중간효과크기가 나타났으며 자살생각과 죽음불안은 작은 효과크기를 보였다. 보호요인으로는 자아존중감이 가장 큰 효과크기를 보였고 자아효능감, 자아통제 순으로 효과크기가 나타났다. 본 연구를 통해서 우울이 노인의 삶의 질에 중요한 영향요인이 되고 있음을 확인할 수 있었으며 노인의 삶의 질 향상을 위해서 우울을 조기발견하고 개입할 수 있는 게이트키퍼의 활용과 찾아가는 상담서비스의 확대가 필요하며 자살생각이나 죽음불안을 경감시키기 위해 죽음준비교육을 일반화시키고 자아존중감을 높이기 위해 노인에게 적합한 일자리를 창출하고 재능기부 및 자원봉사활동 참여 기회의 확대를 제언하였다.